2018
DOI: 10.7150/thno.23848
|View full text |Cite
|
Sign up to set email alerts
|

Dual Chemodrug-Loaded Single-Walled Carbon Nanohorns for Multimodal Imaging-Guided Chemo-Photothermal Therapy of Tumors and Lung Metastases

Abstract: Tumor combination therapy using nano formulations with multimodal synergistic therapeutic effects shows great potential for complete ablation of tumors. However, targeting tumor metastases with nano structures is a major obstacle for therapy. Therefore, developing a combination therapy system able to target both primary tumors and their metastases at distant sites with synergistic therapy is desirable for the complete eradication of tumors. To this end, a dual chemodrug-loaded theranostic system based on singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 73 publications
1
41
0
Order By: Relevance
“…In another study, Zhang and co-authors simultaneously loaded Dox and cisplatin onto polymer modified single walled carbon nanohorns (SWNHs) as a chemo-photothermal theranostic system. 352 Both synergistic effect of Dox and cisplatin and chemotherapy and PTT improved in vitro treatment of 4T1 cancer cells. In vivo study showed that combination of PTT and chemotherapy had the best treatment outcomes.…”
Section: -1 Combining Ptt With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Zhang and co-authors simultaneously loaded Dox and cisplatin onto polymer modified single walled carbon nanohorns (SWNHs) as a chemo-photothermal theranostic system. 352 Both synergistic effect of Dox and cisplatin and chemotherapy and PTT improved in vitro treatment of 4T1 cancer cells. In vivo study showed that combination of PTT and chemotherapy had the best treatment outcomes.…”
Section: -1 Combining Ptt With Chemotherapymentioning
confidence: 99%
“…Combining PTT and chemotherapy can generate improved treatment outcomes. [351][352][353][354][355] In this context, Chen and co-workers developed the supramolecular micelles assembled from polyrotaxane building blocks as a theranostic platform. 351 The axle of polyrotaxane was amphiphilic PDI terminated block copolymer of PEG-b-poly(ε-caprolactone) (PCL), which formed hostguest complexation with the wheel of the primary-amino-containing β-cyclodextrin (β-CD-NH 2 ).…”
Section: -1 Combining Ptt With Chemotherapymentioning
confidence: 99%
“…As such, the sustained release speed has been reported to vary depending on carbon material surface structure or ambient pH. [27][28][29][30] Although anticancer agent release can be slowed by regulating carbon nanober surface structure and ambient pH, this approach remains to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of polymers such as amphiphilic lipid-based poly (ethylene glycol) has also been suggested to produce water-stable SWCNH through non-covalent functionalization [ 40 ]. Similarly, another recent study has proposed to modify SWCNHs with poly (maleic anhydride- alt -1-octadecene) and methoxypolyethylene glycol-b-poly( d , l -lactide), to sequentially load different drugs for combined chemo-photothermic therapy [ 41 ]. Other authors have used a block polyelectrolyte wrapping strategy for the development of a soluble nanohybrid, stable for several months.…”
Section: Single-walled Carbon Nanohorns (Swcnh)mentioning
confidence: 99%